Stem Cell Therapy in Lysosomal Storage Diseases - Boelens, Jaap Jan.; Wynn, Robert. (Stem Cell Biology and Regenerative Medicine, 2013)
Stem Cell therapy for lysosomal diseases (LSDs) is developing rapidly. This volume discusses the history, current practice and future perspectives of stem cells in inborn errors of metabolism (IEM) and provides an international perspective on progress, limitations, and future directions (e.g. gene therapy, iPS, ES) in the field. Beginning with an overview of these diseases, the book covers the breadth of this topic from treatment options, bone marrow transplantation, and alternative treatment options, through long-term outcomes and future perspectives.